Becoming Québécois: Édouard and the Duchesse de Langeais between Old Worlds and New in the work of Michel Tremblay. Issue 2 (1st September 2021) - Killick, Rachel
Abstract : Our identity is formed in large part by the way we see others and the way others, in their turn, see us. This is true both of Québec and of Édouard, one of the principal characters of the fictionalised Montréal universe of Michel Tremblay. A representative of the pre-1970s socio-economic inequality of French-Canadians, Édouard is further marginalised by his homosexuality. In his transvestite persona as the Duchesse de Langeais, a revised version of a Balzacian heroine, he undertakes a mocking critique of the injustices of his society from the 'external' point of view of this supposed French aristocrat before seizing the opportunity of an actual visit to France, hoping to find there a freer and more equitable society. But the Old World turns out to be unwelcoming and antiquated, making Édouard more aware of the hitherto unperceived advantages of his life in Montréal. Returning home, his only option is to resume his role as a provocative duchess, preparing the ground for the advent in 1976 of a modern Québec, a francophone society of the New World, internationally recognised for its openness of mind and its cultural dynamism.